Digital Marketing and Building a Business Network for Indonesian Migrant Workers in Malaysia - Herni Justiana Astuti; Irawan Randikaparsa (Universitas Muhammadiyah Purwokerto, 2023)
Indonesia is one of the countries sending migrant workers to Malaysia. The economic situation is one of the reasons they want to improve their lives when they work in that country. However, they experienced many problems when they returned to Indonesia. Lack of opportunity to work in Indonesia and lack of preparation in doing business is one of the problems when returning to Indonesia. In the digital era, doing business does not have to be with large capital, as long as there is assistance and building a clear network that can help develop a business. This community service aims to make the Indonesian migrant workers in Kuala Lumpur who take part in this community service have insight into digital marketing and build business networks. The method in this service is face-to-face and delivery of material by academics from the Muhammadiyah University of Purwokerto.